Sustainable Supply Chain Management in the Direction of Economy and Civilization Development - Hadri Hasan (International Journal of Supply Chain Management, 2020)
Abstract— Sustainable supply chain management (SSCM) during indict of create bright intellectual generation capable of solving various problems in the economy and community. Different views of a chain value often have an impact on the attitude and manner of decision making and an economic problems. The research attempts to express how the sustainable supply chain management in addressing the diversity of SSCM beliefs as well as their impact in front of economy and society situation. Logistics as well as supply chain management has been regarded to be the crucial factor for the companies to obtain competitive edge. This indicates that the SSCM is able to respond to the difference of view as a diversity of belief. Therefore in this paper, we provide a tutorial on the current research of operations management of logistics and supply chain